CORRELATES OF ADEQUACY OF RETIREMENT BENEFITS AMONG THE OLDER PERSONS IN NIGERIA - Wahab Elias Olukorede; U. C. Isiugo-Abanihe (European Scientific Journal, ESJ, 2012)
Background--It is unknown how socio-demographic variables impact on adequacy of gratuity among the older persons inNigeria. This has become essential in order to improve the preparation for old age among Nigerians. Reliable information isalso required to formulate comprehensive social security system for the elderly. Methods - Quantitative data was collectedthrough individual-based questionnaire. Multi-stage sampling procedure was employed to select local government areas,enumeration areas and individuals for the study. In all, 810 respondents were interviewed. Findings - In the female model,the result indicates that aged 60-64 years are 62 percent less likely to, those aged 65-69 are 72 percent less likely to havereported adequate gratuity than those aged 70 years and above. As regards education, those with primary education are 95percent less likely to report adequacy of gratuity than those with secondary education. With respect to religion, whileChristians are 1.3 times more likely to, Muslims are 1.4 times more likely to report adequate gratuity than those who areadherents of African traditional religion. Finally, while those with 1-3 children are 3.4 times more likely to, those with 4-6children are 1.9 times more likely to report adequate gratuity than those with seven or more children. Conclusion - The ideathat old-age security and well being in Nigeria should remain the primary responsibility of the family is untenable.Government must assume the primary responsibility in a partnership in which the family also continues to play a significantrole.